Marxism and Class-Based Analysis in the Body of Knowledge: The Scientometric Analysis and Research Agenda - Ansar, Muhammad Chaeroel (Glocal Society Journal, 2024)
This study provides a comprehensive scientometric analysis to examine the incorporation and impact of Marxist theory and class-based analysis within the broader academic knowledge base. By utilizing Scientometric data from renowned scientific databases covering the last seventy years, we can pinpoint important patterns, notable authors, essential publications, subject groups, and relevant keywords relating to Marxism and class analysis. These findings show increasing interest in the topic, especially after the 2000s. This analysis emphasizes the importance of theoretical study and the working class as topics that often appear in recent research. Additionally, we analyze the distribution of research output and country collaborations, observing substantial clustering in the Americas and the United Kingdom. Despite increasing interest in this topic, our analysis reveals gaps in existing research, namely in the practical implementation and integration of different disciplines. Based on these observations, we suggest a study plan that prioritizes the need for more detailed empirical investigation, examination of social class dynamics in non-Western settings, and the incorporation of Marxist analysis into current topics such as globalization and the working class. This agenda aims to increase the significance and practicality of class-based analysis in understanding contemporary socio-economic phenomena.